Effect of Moderate-Intensity Exercise on Plasma C-Reactive Protein and Aortic Endothelial Function in Type 2 Diabetic Mice - Nada Sallam; Majid Khazaei; Ismail Laher (Mediators of Inflammation)
The aim of this study was to evaluate the effects of moderate-intensity exercise on plasma levels of C-reactive protein (CRP) and tumor necrosis factor-alpha (TNF-α) as markers of low-grade inflammation and endothelial function in diabetic (db/db) mice. Control and db/db mice were divided into sedentary and exercised groups. Aortic endothelial function was evaluated after two- and six-week exercises using a wire myograph. Plasma CRP levels were measured at baseline, and after two and six weeks of exercise. Baseline plasma CRP levels were significantly higher in db/db mice compared to control (P<.05). After two weeks of exercise, aortic endothelial function was significantly improved without affecting body weight or plasma CRP levels. Six weeks of exercise not only improved endothelial function, but also significantly reduced body weight and plasma CRP levels in db/db mice. Thus short-term exercise has beneficial effect on endothelial function without reducing low-grade inflammation while more prolonged exercise periods are required to reduce inflammatory markers.